1979
DOI: 10.1111/j.1476-5381.1979.tb08669.x
|View full text |Cite
|
Sign up to set email alerts
|

The Failure of Indomethacin to Alter Acth‐induced Adrenal Hyperaemia or Steroidogenesis in the Anaesthetized Dog

Abstract: The response of adrenal blood flow to adrenocorticotropic hormone (ACTH) was measured with radioactive microspheres in anaesthetized, dexamethasone‐treated, mongrel dogs. Adrenocorticotropic hormone (2 u/h i.v.) increased adrenal blood flow within 15 min and this persisted for the duration of the infusion. Cortisol concentrations also rose with ACTH infusion. Indomethacin (6 mg/kg i.v. followed by 1 mg/min) did not affect the adrenal response to ACTH although plasma concentrations of indomethacin (21.9 ± 2.5 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The action of ACTH or stress in increasing perfusion medium flow through the gland is in agreement with other physiological (Balfour, 1953;Hartman et al 1955;Sapirstein & Goldman, 1959;Stark et al 1965;L'Age et al 1970;Gerber & Nies, 1979) and anatomical studies (Harrison & Hoey, 1960;Rhodin, 1971;Pudney, Sweet, Vinson & Whitehouse, 1981), but the present results further indicate that the property is not shared by all of the effectors tested. In particular, it appears to be a characteristic of the known zona fasciculata stimulants, ACTH and dbcAMP, but not of the specific zona glomerulosa stimulants, potassium ions and angiotensin II, which may indeed have the reverse effect at high concentrations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The action of ACTH or stress in increasing perfusion medium flow through the gland is in agreement with other physiological (Balfour, 1953;Hartman et al 1955;Sapirstein & Goldman, 1959;Stark et al 1965;L'Age et al 1970;Gerber & Nies, 1979) and anatomical studies (Harrison & Hoey, 1960;Rhodin, 1971;Pudney, Sweet, Vinson & Whitehouse, 1981), but the present results further indicate that the property is not shared by all of the effectors tested. In particular, it appears to be a characteristic of the known zona fasciculata stimulants, ACTH and dbcAMP, but not of the specific zona glomerulosa stimulants, potassium ions and angiotensin II, which may indeed have the reverse effect at high concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…The only mechanism which has been proposed to account for the linking of steroidogenesis with blood flow is that the hydrolysis of cholesterol esters consequent on ACTH stimulation releases arachidonic acid which may then be used in the synthesis of prostaglandins (Grant, 1968). However, the consensus of opinion is that prostaglandin production is not increased by ACTH stimulation (Flack, 1973;Swartz, Williams & Butters, 1983), although there are varied reports on the action of indomethacin on ACTH-induced adrenal hyperaemia and steroidogenesis in dogs (Gerber & Nies, 1979;Varga et al 1979). An alternative hypothesis may well require that ACTH itself has direct effects on elements of the adrenal vasculature, perhaps on the capsular/ subcapsular arterioles.…”
Section: Discussionmentioning
confidence: 92%
“…As described earlier, ACTH increases adrenal blood flow in vivo and in perfused adrenals (8,12,15,16,25,27,31,35). Studies by Hinson and colleagues (15,16) suggested that the increase in blood flow is due to the release of histamine and serotonin from perivascular mast cells and the subsequent vasorelaxation induced by these compounds.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, histamine relaxed small adrenal arteries through endothelium-derived NO and prostaglandins. However, ACTH-induced dilation does not involve NO or prostaglandins (6,12). The reasons for these discrepancies are unclear but may represent species variability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation